1985
DOI: 10.1071/ea9850076
|View full text |Cite
|
Sign up to set email alerts
|

Performance of North American and Australian lucernes in the Queensland subtropics. 1. Field reaction to important root and crown diseases

Abstract: Twenty-three lucernes from North America and five Australian lines were assessed for their sensitivity to root rot (Phytophthora megasperma f. sp. medicaginis), anthracnose/ crown rot (Colletotrichum trifolii) and root canker (Rhizoctonia solani). Plantings were spray irrigated or raingrown on sites representative of the major lucerne environments in southern Queensland. Ratings for each disease discriminated generally the same most susceptible and resistant lines across plantings, although significant sitexli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Pastoral industries have played an important role in the post-European settlement history of Queensland. A general history of the pastoral settlement, development and subsequent changes to native pastures and vegetation in Queensland is provided by Craig (1925), Gramshaw and Lloyd (1993) and Lloyd and Burrows (1987) The full economic potential of the cattle industry was only established in times of market security and/or access, which was achieved during 1914-1920 and 1939-1945 when export demand and market quotas combined to force beef prices higher (Daly 1980). However, profitability of beef enterprises was not as high for wool production, leading to consolidation of the wool industry in the central and southern interior of Queensland.…”
Section: Introductionmentioning
confidence: 99%
“…Pastoral industries have played an important role in the post-European settlement history of Queensland. A general history of the pastoral settlement, development and subsequent changes to native pastures and vegetation in Queensland is provided by Craig (1925), Gramshaw and Lloyd (1993) and Lloyd and Burrows (1987) The full economic potential of the cattle industry was only established in times of market security and/or access, which was achieved during 1914-1920 and 1939-1945 when export demand and market quotas combined to force beef prices higher (Daly 1980). However, profitability of beef enterprises was not as high for wool production, leading to consolidation of the wool industry in the central and southern interior of Queensland.…”
Section: Introductionmentioning
confidence: 99%
“…An extrapolation was therefore required to standardise the Gilruth Plains wool production data to the 1992 standard. This was a reasonable assumption given Gramshaw and Lloyd (1993) showed a consistent increase in Queensland fleece weights from the tum of the century to the present day.…”
Section: ^ _omentioning
confidence: 71%
“…Reviews of the Queensland wool industry identified the major sources of variability in production as limitations to the spatial distribution of the wool industry, and the impact of seasonal climate variability on wool production, reproduction and mortality (Farmer et al 1947, Reid and Thomas 1973, White 1978, Orr and Holmes 1984, McMemman 1985, Gramshaw and Lloyd 1993. Since the 1940's, intensive field trials have been conducted throughout western Queensland to examine the interaction of management options, pastures, and climate variability on animal production.…”
Section: Qld Wool Production 1952-1992^mentioning
confidence: 99%